Preparation and Characterization of Lithium Zirconium Silicate for CO2 Capture - T. S. Bhosale; A. G. Gaikwad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The samples of lithium zirconium silicate were prepared by precipitation, template and sol-gel meth-ods. The samples were prepared with several mol ratios of Li:Zr:Si. The preparation of lithium zirco-nium silicate samples by precipitation method were carried out by using the lithium nitrate, zirconyl nitrate, zirconium(IV) oxypropoxide and tetramethylorthosilicate (TEOS) as precursors. The samples of lithium zirconium silicate were prepared by using cetyltrimethyl-ammonium bromide (C-TAB) and tetramethyl ammonium hydroxide (TMAOH) by template method. The samples of lithium zirconium silicate were characterized by XRD, TEM, SEM, 29Si-MAS NMR and FTIR. The surface area, alkalinity / acidity of the samples of lithium zirconium silicate were measured. The TGA analysis of lithium zirco-nium silicate samples was done. The CO2 captured by the samples of lithium zirconium silicate was es-timated. The captured CO2 by the samples of lithium zirconium silicate was found to be in the range 3.3 to 8.6 wt%. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)